Direct numerical simulation of transverse ripples. 2. Self‐similarity, bedform coarsening, and effect of neighboring structures - Zgheib, N. (2018)
Coupled bed‐flow direct numerical simulations investigating the early stages of pattern formation and bedform (ripple) interactions were examined in a previous paper (Part 1), making use of the resolved flow field. In this paper (Part 2), we compare our results to published experimental data and provide an extensive quantitative analysis of the bed using spectral analysis and two‐point correlations. The effect of the mobile rippled bed on the flow structure and turbulence is investigated locally (at specific streamwise locations) and over the entire computational domain. We show that developing ripples attain a self‐similar profile in both the shape and the corresponding bed shear stress. We demonstrate the importance of neighboring structures, especially upstream neighbors, on bedform dynamics in terms of the growth, decay, and speed of ripples. Finally, we examine the defect‐free interactions in the later stages of bed evolution, which primarily lead to wave coarsening.